Phasenschieber für satellitenfunkempfänger-frontends / A phase shifter for satellite radio receiver frontends - Rascher, Jochen; Ußmüller, Thomas (GMM Fachbericht 70: ANALOG 2011, 2011)
In this publication the advantages of passive phase shifters are shown which can be used in integrated satellite radio receiver frontends at 2.3GHz center frequency. High large signal robustness, low temperature dependency, and low inser- tion loss <1dB per phase bit can be achieved. The 3 bit phase shifter design uses FET switches in resistive body floating technique for that.
elib2cris::1512001600,rascher2011